Reseña del libro Costos para la gestión, de Beatriz Lucero, Zulma Luparia, Susana Medina y Mauro Pérez Vaquer Santa Rosa: EdUNLPam, 2017, ISBN 978-950-863-307-1 (Costos y Gestión, 2020)
Miguel Lissarrague